Synergistic Effects of the Westerly and Asian Monsoon on Summer Rainfall in the Tarim Basin of Northwest China Under Different Climate Backgrounds - Lixia Meng; Qiang Zhang; Shujuan Hu (International Journal of Climatology, 2026)
Based on the Japanese 55‐year Reanalysis (JRA‐55) atmospheric circulation data provided by the Japan Meteorological Agency and monthly rainfall data from 28 meteorological stations across the Tarim Basin in Northwest China extracted by the China Meteorological Data Network from 1961 to 2022, the synergistic effects of the westerly and Asian monsoon on summer rainfall in the Tarim Basin are investigated. Results show that summer rainfall in the Tarim Basin has experienced a significant interdecadal increase over the past several decades and can be divided into two periods: A dry period (1961–1987) and a wet period (1988–2022). Under different climate backgrounds, the atmospheric circulations associated with the summer rainfall anomaly show obvious differences. The westerly indicated by the Silk Road Pattern (SRP) correlates well with the summer rainfall in the two periods, but the South Asian summer monsoon (SASM) (East Asian summer monsoon, EASM) is only well related to the summer rainfall in the dry period (wet period). In the dry period, the strengthened SRP and weakened SASM are associated with the southward movement of the subtropical westerly jet (SWJ) over Central Asia (CA). Meanwhile, the anomalous cyclone over CA and the anomalous anticyclone over the Arabian Sea strengthen the transport of water vapour from the Arabian Sea to the Tarim Basin. So, the Tarim Basin receives more summer rainfall. During the wet period, the strengthened SRP and weakened EASM as represented by the strengthened EAP atmospheric teleconnection can result in the SWJ moving northward over East Asia. Meanwhile, in conjunction with an anomalous anticyclone over the Mongolian Plateau, the westward extension of the West Pacific Subtropical High enhances the transport of water vapour from the Bay of Bengal to the basin. As a result, the Tarim Basin generates more summer rainfall.